Basic of CMOS cell design - Sicard, Etienne (McGraw-Hill, 2007)
Electronic circuit designers and electronic engineering students can turn to Basics of CMOS Cell Design for a practice-based introduction to the design and simulation of every major type of CMOS (complementary metal oxide semiconductor) integrated circuit. You will find step-by-step explanations of everything they need for designing and simulating CMOS integrated circuits in deep-submicron technology, including MOS devicesinvertersinterconnectsbasic gates arithmeticssequential cell designand analog basic cells. The book also presents design rules, Microwind program operation and commands, design logic editor operation and commands, and quick-reference sheets.